Nature of bistable states in the case of anodic dissolution of metals in multicomponent electrolytes. - Pototskaya, V.V.; Volkov, S.V.; Omel’chuk, A.A. (Украинский химический журнал, 2005)
A theoretical model is proposed, which describes the mechanism of the anodic dissolution of metals in multicomponent electrolytes. The relation between chemical reaction and transport processes may give rise to two stable states in the electrochemical system. It has been shown that in the case of controlling the rate of the mass transfer process in electrochemical systems with a number of components of ≥ 3, the outer Helmholtz plane potential may take on two values at the same electrode potential value. The question of the appearance of anodic dissolution limiting currents has been studied for electrolytes containing four sorts of ions with arbitrary charges and diffusion coefficients. The existence and magnitude of limiting current are also dependent on the charge of the complex formed.